Effects of pollution on dormant-stage banks of cladocerans and rotifers in a large tropical reservoir - Coelho, Paula Nunes [UNESP]; Paes, Thécia Alfenas Silva Valente; Maia-Barbosa, Paulina Maria; dos Santos-Wisniewski, Maria José (Springer Nature, 2021)
Here, we describe the abundance and composition of the dormant-stage banks of cladocerans and rotifers at two locations in a tropical reservoir (Furnas Reservoir, Minas Gerais, Brazil) that are subject to different anthropogenic impacts. We hypothesized that at the site that received sewage, the density of resting eggs would be higher, but the species richness would be lower. Sediment samples were collected monthly at the two sampling stations. We counted the number of dormant stages and performed hatching experiments in the laboratory. Combining both sampling locations, we found a total of 26 species, 16 cladocerans, and 10 rotifers. Our hypothesis was partially corroborated, since the abundance and richness of dormant stages were significantly higher in the location subjected to wastewater release. Environmental pollution resulting from wastewater release and the cultivation of tilapia in cages is the most likely factor contributing to the higher values of egg density at this location. In contrast, the presence of aquatic macrophytes (a possible result of nutrient enrichment) at the same site may have contributed to the increase in species richness. Finally, our study indicates that the wastewater release in the reservoir can affect the production of dormant stages by cladocerans and rotifers.
Keywords: Diapause; Eutrophication; Furnas Reservoir; Resting eggs; Wastewater; Zooplankton